27 Early and mid term outcomes after transaortic catheter valve implantation (TAVI). (7th October 2015) - Bajrangee, A; Coughlan, JJ; Teehan, S; Musafa, G; Murphy, R; O'Connor, C; Quinn, M; Sriniva, P; Coleman, G; Maree, A; Crean, P
Abstract : Aim: Transcatheter aortic valve implantation (TAVI) has become a therapeutic option for high-risk or nonoperable patients with severe symptomatic aortic valve stenosis. We reviewed our patient cohort analysing early and mid term outcomes. Methods: Records of 147 patients who underwent TAVI between 12/08 and 12/14 at St James Hospital and Blackrock Clinic. A database of baseline demographics, pre procedural and procedural characteristics and complications was created. Contacting patients, next of kin or the primary care doctor confirmed clinical follow up and pacing rates after discharge. Results: 147 patients underwent TAVI with a mean age of 82 (SD-5), with 56% males (83/147). 87 received a Corevalve and the remaining 61 an Edwards prosthesis. Mean EURO II score was 9.2 ± 6.46 for the total cohort. Table 1 further illustrates baseline demographics. Access was via transfemoral route 135/147 (91%), trans apical or transaortic in (7%) and subclavian in (3%). Mean length of stay was 9.97 days. Major vascular complications occurred in 18 cases (12.2%) and pacing rates post implant was 13.5% of which 90% were Corevalve implants (P < 0.001). Cerebrovascular insults occurred in 8 patients (5.4%). At 30 days 9.52% of patients had died, 3 intraoperatively. One-year and two year mortality was 17% and 32.5% respectively. Of overall deaths cardiac causes were implicated in 71% (10/147) at 30 days (P < 0.01). At one year and two years death due to cardiac etiologies had occurred in 18.18% and 49% of dead patients respectively. The strongest predictor of death at one year was a GFR <30 mls/min (p = 0.001). Whilst aortic regurgitation grade improved from 1.31 to 0.89 this did not correlate with mortality at one year (p = 0.09). Left ventricular function also showed an improvement at six months of 1.9 ± 1.2 by Simpsons method but this has not been indicative of increased survival to date. Conclusion: This analysis represents one of the first in Ireland evaluating mortality and morbidity post TAVI implantation. When compared to international data our rates of survival and complications continue to be favourable.